2018
DOI: 10.1186/s40409-018-0173-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of toad Rhinella schneideri skin glands and partial biochemical characterization of its cutaneous secretion

Abstract: BackgroundAnimal poisons and venoms are sources of biomolecules naturally selected. Rhinella schneideri toads are widespread in the whole Brazilian territory and they have poison glands and mucous gland. Recently, protein from toads’ secretion has gaining attention. Frog skin is widely known to present great number of host defense peptides and we hypothesize toads present them as well. In this study, we used a RNA-seq analysis from R. schneideri skin and biochemical tests with the gland secretion to unravel it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The only protein that we would call the attention is the antimicrobial peptide precursor (Additional file 1: fractions 3 and 4; Additional file 2: fraction 5). Recently, Shibao et al [41] identified several classes of antimicrobial peptides in Rhinella schneideri skin glands by transcriptomic analysis. However, complementary studies are still necessary to confirm the actual existence of them.…”
Section: Discussionmentioning
confidence: 99%
“…The only protein that we would call the attention is the antimicrobial peptide precursor (Additional file 1: fractions 3 and 4; Additional file 2: fraction 5). Recently, Shibao et al [41] identified several classes of antimicrobial peptides in Rhinella schneideri skin glands by transcriptomic analysis. However, complementary studies are still necessary to confirm the actual existence of them.…”
Section: Discussionmentioning
confidence: 99%
“…The lower temperature condition is known to attenuate the neuromuscular blockade by Bothrops PLA 2 neurotoxins (Cogo et al, 1998;Ponce-Soto et al, 2009;Floriano et al, 2013;Sucasaca-Monzón et al, 2015). Although there is evidence of the presence of PLA 2 enzymes in the mucous gland secretions of R. schneideri toad (Shibao et al, 2018), the same was not observed in the poison of this species. However, incubation at lower temperatures abolished the neuromuscular blockade in BC preparations while a mild and progressive neuromuscular facilitation was observed in 60 min exposure time.…”
Section: Discussionmentioning
confidence: 89%
“…Mucus-rich samples, such as toad and frog poisons, is also another issue, which may hinder the use of omic approaches (Shibao et al, 2018). In this context, studies comprising animal toxins are not a simple task since many challenges must be addressed.…”
Section: Challenges Regarding Basic Researchmentioning
confidence: 99%